Effect of lisinopril and perindopril on serum lipid profile in Albino rabbits - Chandra, Shruti; Singh, S. P.; Singh, Rashmi; Agarwal, Neeraj Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Hypertension with dislipidemia is becoming a common morbidity, since ACE inhibitors are the first line of antihypertensive drugs so present study was undertaken with the aim to evaluate the possible effects of ACE inhibitor on lipid profile in albino rabbits. Methods: The study was conducted in the Department of Pharmacology and Therapeutics, GSVM Medical College, Kanpur. Rabbits were divided into 2 groups with 6 in each group. Rabbits of Group I was given Lisinopril in dose of 0.25mg/kg and of group II was given Perindopril in dose of 0.20mg/kg for a period of 6 weeks. Lipid profile estimation (Serum Total cholesterol, serum HDL, serum LDL, serum Triglycerides and serum VLDL) was done at day 0, 7, 21 and 45 respectively. Results: After analysis Rabbits of group-I (Lisinopril) showed 3.1% decrease in serum cholesterol level at 45th day (P<0.001). Serum HDL level increased by 6.4% and 14.3% at day 21 and 45 respectively (P<0.05). Increase in serum Triglyceride level was 2.6% at day 45 (P>0.05). Serum LDL level decreases by 4.4% and 8.6% at day 21 and 45 respectively (P<0.001). There was no significant change in Serum VLDL level. Rabbits of group- II (Perindopril) showed decreased total cholesterol levels by 2.6% (P<0.05). There was an increase in HDL level by 6.8 % at day 45(P<.05). Triglycerides and VLDL levels were not significantly altered while serum LDL level decreases by 6.7% at day 45 (P<0.01). Conclusions: From our study it was concluded that Lisinopril had a favourable effect on serum lipid profile by decreasing total cholesterol, increasing serum HDL level. It may increase triglycerides, decrease LDL. Perindopril increase serum HDL and decreases LDL, there is no significant change in cholesterol, TG and VLDL levels.